Implementasi Metode Visekriterijumsko Kompromisno Rangiranje (VIKOR) dalam Sistem Penunjang Keputusan Berbasis Web Untuk Penentuan Karyawan Terbaik (Studi Kasus: Prime Parking Polda Metro Jaya) - Witry Eviliah Gumay; Nardiono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Prime Parking is one of the companies engaged in the management of parking services in Indonesia. To improve the quality of profits and the progress of the company, one of the programs implemented by the company is the welfare of its employees through several programs, including realizing the best employees. But in the best implementation, companies often experience problems in performing calculations, they still perform calculations manually using the form of performance appraisal and are analyzed manually. So it is considered less efficient because the data processing will take a long time and less accurate. There is an inaccuracy in giving value to employees which has a negative impact and creates social jealousy among employees. Therefore, it is hoped that the decision-making process can be assisted by a computerized decision support system using the Visekriterijumsko Kompromisno Rangiranje (VIKOR) method which is suitable for linear ranking, so subjectivity in decision making is expected to be reduced or even eliminated. So that the selection can be done objectively for the company's progress in the future.